Analysis of drug interactions with serum proteins and related binding agents by affinity capillary electrophoresis: A review. Issue 23 (10th November 2022) - Sharmeen, Sadia; Kyei, Isaac; Hatch, Arden; Hage, David S.
Abstract: Biomolecules such as serum proteins can interact with drugs in the body and influence their pharmaceutical effects. Specific and precise methods that analyze these interactions are critical for drug development or monitoring and for diagnostic purposes. Affinity capillary electrophoresis (ACE) is one technique that can be used to examine the binding between drugs and serum proteins, or other agents found in serum or blood. This article will review the basic principles of ACE, along with related affinity‐based capillary electrophoresis (CE) methods, and examine recent developments that have occurred in this field as related to the characterization of drug–protein interactions. An overview will be given of the various formats that can be used in ACE and CE for such work, including the relative advantages or weaknesses of each approach. Various applications of ACE and affinity‐based CE methods for the analysis of drug interactions with serum proteins and other binding agents will also be presented. Applications of ACE and related techniques that will be discussed include drug interaction studies with serum agents, chiral drug separations employing serum proteins, and the use of CE in hybrid methods to characterize drug binding with serum proteins.